Analisis Peraturan Presiden Mengenai Investasi pada Bidang Usaha Minuman Keras dalam Perspektif Hukum Moral dan Agama - Surnata Surnata; Fadjrin Wira Perdana; Irwan Irwan; Doharmam Lumban Tungkup; Miran Miran (Jurnal Indonesia Sosial Sains, 2022)
The president as an executive agency can make regulations called presidential regulations (Perpres). The formation of the Presidential Regulation is used as a guideline by citizens in carrying out their daily lives. Unfortunately, not all presidential regulations are in line with religion and moral law so that they get pros and cons from the public, as is the case with Presidential Decree No. 10 of 2021 concerning the Investment Business Sector, to be precise in appendix 2 regarding liquor investment. This study was conducted to analyze the presidential regulation from the perspective of moral and religious law. This research was conducted with a qualitative approach through the type of normative juridical research and delivered descriptively. The technique of collecting data is through literature review, interviews, observation and distributing questionnaires through the g-form. Based on the results of the study, it is known that Presidential Decree No. 10 of 2021 concerning the Investment Business Sector, precisely in Appendix 2 regarding investment in liquor is contrary to Islamic religious law. Whereas in the moral law there are pros and cons, the cons are more than the pros. This is proven by the repeal of this Presidential Regulation and the issuance of Government Regulation No. 49 of 2021 regarding Amendments to Presidential Regulation No. 10 of 2021 concerning the Investment Business Sector.